Analisis Perancangan Tata Letak Minimarket Malabar di Kota Bogor Dengan Pendekatan Activity Relationship Chart (ARC) - Isma Nurjanah; Chintya Eka Putri; Anie Puspita Sari; Muhammad Rifa Zainur Ridha (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Retail business is a business that sells a variety of products, such as daily necessities, household needs, fashion products, beauty, and electronics. One of the important factors that retailers must pay attention to in order to attract buyers to come to the store is layout management. Therefore, this research aims to analyze the layout of space in one of the retail stores located in Bogor, namely Minimarket Malabar so that its operational activities are optimal. This research was conducted using the Activity Relationship Chart (ARC) and Total Closeness Rating (TCR) methods. ARC and TCR analysis shows that the display room becomes the highest space value of 168, meaning that the room is the most important and influential on Minimarket Malabar, so it must be in a strategic place. And the toilet becomes the lowest value of 6 which means that the toilet does not have an important influence on the layout of the Malabar Minimarket space to optimize operational activities.